PENGARUH KUALITAS LAYANAN DAN KEPUASAN PELANGGAN TERHADAP MINAT PEMBELIAN ULANG PADA INDUSTRI RETAIL - Tries Edy Wahyono (Journal of Management and Business, 2006)
Retail industry required to improve service quality continually to cope the high competitiveness and the customer demand. Theoritically, service quality will produce customer satisfaction, and the satisfied custiomer will doing repurchase or repurchase buying intention.